2022
DOI: 10.3389/fpls.2022.815011
|View full text |Cite
|
Sign up to set email alerts
|

N-Induced Species Loss Dampened by Clipping Mainly Through Suppressing Dominant Species in an Alpine Meadow

Abstract: Nitrogen addition and clipping can exert substantial impact on species diversity but their interactions and the underlying mechanisms still remain unclear. Resource competition theory holds that sufficiently strong competitive ability of dominant species can lead to the losses of subordinate species through competitive exclusion, while niche differentiation theory suggests that the persistence of subordinate species in competitive systems can be promoted by guaranteeing positive growth rates of rare species. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…However, at the abundance gradient, the abundant subgroup owns a small number of OTUs species and a high abundance ratio, while the rare subgroup showed the opposite. Some studies also showed that the total number of sequences of abundant subgroup was dominant while the species number of rare subgroup was absolutely dominant 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at the abundance gradient, the abundant subgroup owns a small number of OTUs species and a high abundance ratio, while the rare subgroup showed the opposite. Some studies also showed that the total number of sequences of abundant subgroup was dominant while the species number of rare subgroup was absolutely dominant 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Then the zero distribution of the niche width index was calculated for each OTU. Based on the consensus that habitat-generalized subgroup owe a wider niche width than the habitat-specialized subgroup 40 , OTUs were classified into a habitat-generalized or a specialized group based on whether the frequency of observed occurrence exceeded the upper 95% confidence interval or fell below the lower 5% confidence interval, and the OTUs were distributed to the habitat-neutral group if the observed niche width was within in the 5% to 95% confidence interval range 18 . …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation